The Influence of Leadership Style, Work Environment and Compensation on Job Satisfaction in High Schools - Akhmad Afandi; Hasan Ubaidillah (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of Leadership Style, Work Environment and Compensation on employee job satisfaction either partially or simultaneously. This research was conducted with quantitative methods. The target population in this study were all employees at SMA Muhammadiyah 2 Sidoarjo, totaling 122 employees. The data collection technique used is a questionnaire with a sample of 103 people. The data analysis technique used in this study is multiple linear regression using SPSS version 22 for windows. Based on the results of data analysis, it was found that there was an influence of Leadership Style, Work Environment and Compensation on Job Satisfaction at SMA Muhammadiyah 2 Sidoarjo. The implementation of the results of this research analysis is as input for the company on the subject matter that has been adapted to the existing theory.